Effects of diesel injection pressure on the performance and emissions of a HD common-rail diesel engine fueled with diesel/methanol dual fuel. (15th January 2015) - Liu, Junheng; Yao, Anren; Yao, Chunde
Highlights: The common-rail diesel engine was fueled with diesel/methanol dual fuel. Increasing injection pressure would improve fuel economy of DMDF engine. Effect of injection pressure on DMDF combustion characteristic was analyzed. Effect of injection pressure on emissions of DMDF engine was investigated. Abstract: The diesel/methanol dual fuel (DMDF) combustion mode was conducted on a turbo-charged, inter-cooling diesel engine with 6-cylinder for the heavy duty (HD) vehicle. In DMDF mode, methanol is injected into the intake port to form lean air/methanol premixed mixture, and then ignited by the direct-injected diesel fuel in cylinder. This study is aimed to investigate the effect of diesel injection pressure on the characteristics of performance and exhaust emissions from the engine with common-rail fuel system. The experimental results show that at low injection pressure, the IMEP of DMDF mode is lower than that of pure diesel combustion (D) mode. COVIEMP of DMDF mode firstly decreases and then increases with increasing injection pressure, and it remains under 2.1% for all the tests. It is found that the combustion duration in DMDF mode becomes shorter, the maximum cylinder pressure and the peak heat release rate increase, and CA50 gets close to the top dead center as the injection pressure increases. BSFC of DMDF mode decreases with the increase of injection pressure, and is lower than that of D mode for injection pressure over 115 MPa. Both of NOX and smoke emissions are reduced in DMDF mode. But smoke decreases and NOX increases as the diesel injection pressure increases in DMDF mode. DMDF generates lower NO and CO2 emissions, while produces higher HC, CO, andNO2 emissions compared to D mode. As the diesel injection pressure increases, CO and HC emissions are decreased, however, CO2 and NO2 emissions are slightly increased.